2019
DOI: 10.1051/0004-6361/201834840
|View full text |Cite
|
Sign up to set email alerts
|

Gas infall and possible circumstellar rotation in R Leonis

Abstract: We present new interferometer molecular observations of R Leo taken at 1.2 mm with the Atacama Large Millimeter Array with an angular resolution up to ≃0·″026. These observations permit us to resolve the innermost envelope of this star revealing the existence of a complex structure that involves extended continuum emission and molecular emission showing a non-radial gas velocity distribution. This molecular emission displays prominent red-shifted absorptions located right in front to the star typical of materi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In recent years there has been a strong focus on investigating the isotropy of the mass-loss process in low-to intermediate mass evolved stars, which was partly expedited by the superior imaging capabilities of ALMA. Several AGB sources with previously known complex circumstellar dynamics and/or binary companions have been mapped in detail (e.g., Decin et al 2015;Maercker et al 2016;Doan et al 2017;Kim et al 2017;Homan et al 2018;Fonfría et al 2019). With the DEATHSTAR project, the aim is to get an overview of how widespread and significant the detected asymmetrical features are, from the perspective of measuring the amount of circumstellar wind material.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years there has been a strong focus on investigating the isotropy of the mass-loss process in low-to intermediate mass evolved stars, which was partly expedited by the superior imaging capabilities of ALMA. Several AGB sources with previously known complex circumstellar dynamics and/or binary companions have been mapped in detail (e.g., Decin et al 2015;Maercker et al 2016;Doan et al 2017;Kim et al 2017;Homan et al 2018;Fonfría et al 2019). With the DEATHSTAR project, the aim is to get an overview of how widespread and significant the detected asymmetrical features are, from the perspective of measuring the amount of circumstellar wind material.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Instead, these line profiles are anomalous. Some are previously known to be anomalous, for example, L 2 Pup (e.g., Kervella et al 2016) and R Leo (Fonfría et al 2019), while others have not been studied with a focus on the detailed structure of the CSE, for example, R Hya and SS Vir.…”
Section: Indications Of Circumstellar Anisotropic Structurementioning
confidence: 99%
“…morpho-kinematics than had been originally anticipated. It has been the case with Mira for now many years, recent examples are QX Pup (Sánchez Contreras et al 2018;Olofsson et al 2019), R Aqr (Ramstedt et al 2018) and R Leo (Fonfria et al 2019), raising new questions that are still awaiting an answer. In the present case of R Dor, several such questions are present: the motor of the inner rotation providing the required angular momentum is unknown; Vlemmings et al (2018) and Homan et al (2018) argue for the presence of a close by companion but we have no evidence for its existence and a magnetic field origin is an-other possibility (Matt et al 2000); a detailed study of the strong absorption observed in the blue-shifted hemisphere, in particular for the SiO emission line, possibly including a contribution from in-falling gas, needs still to be done; the dynamics underlying the emission of the radial outflows revealed in the present work is not understood; the nature of the high Doppler velocity components, apparently unrelated to other observations, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the low gravity of AGB stars causes the extended atmosphere to be affected by convective processes that lead to asymmetric structures, hot spots, and highdensity clumps. This complex morphology is predicted by 3D hydrodynamical simulations (Freytag et al 2017) and is starting to be characterized in detail with high angular resolution observations at infrared and (sub-)millimeter wavelengths (e.g., Khouri et al 2016;Vlemmings et al 2017;Fonfría et al 2019).…”
Section: Radial Profiles Of Temperature and Pressurementioning
confidence: 96%